Genetic basis of dilated cardiomyopathy. (1st December 2016) - Pérez-Serra, Alexandra; Toro, Rocio; Sarquella-Brugada, Georgia; de Gonzalo-Calvo, David; Cesar, Sergi; Carro, Esther; Llorente-Cortes, Vicenta; Iglesias, Anna; Brugada, Josep; Brugada, Ramon; Campuzano, Oscar
Abstract: Dilated cardiomyopathy is a rare cardiac disease characterized by left ventricular dilatation and systolic dysfunction leading to heart failure and sudden cardiac death. Currently, despite several conditions have been reported as aetiologies of the disease, a large number of cases remain classified as idiopathic. Recent studies determine that nearly 60% of cases are inherited, therefore due to a genetic cause. Progressive technological advances in genetic analysis have identified over 60 genes associated with this entity, being TTN the main gene, so far. All these genes encode a wide variety of myocyte proteins, mainly sarcomeric and desmosomal, but physiopathologic pathways are not yet completely unraveled. We review the recent published data about genetics of familial dilated cardiomyopathy. Highlights: Familial DCM is a rare genetic entity with a heterogeneous clinical progression and outcome. NGS technology helps to unravel genetic cause of disease in a cost-effective way. Genotype-phenotype studies are crucial in order to clarify the pathogenic role of new genetic alterations identified. Genetic advances help clinicians to improve current diagnostic tools and management